Arabian monarchies in the regional policies of Islamic Republic of Iran (Journal of Oriental Studies, 2016)
The author of this given article titled explores the foundations of Irano-Arabic relations. After the achievement of Islamic Revolution in the country, a principle of exportation of Islamic Revolution abroad was taking place in the sphere of external affairs of Iran which resulted in weakening of relations with the Arabian states. However, during the political regime of the reformists as A.А. Hashemi-Rafsanjani and M. Hatami relations between Iran and Arabic countries was getting a better shape. But the atomic programme of Iran aswell as the regional policies of the USA in the Arabic world at present time, can be seen as a barrier for enhancing Irano-Arabic bilateral relations.